ASSESSMENT OF DYNAMIC CHARACTERISTIC OF UNSTABLE OBJECT AT CONSTANT REGIME - Vovk, V.; Shevchuk, D.; Macuk, N.; Borisenko, M. (Proceedings of National Aviation University (archive), 2012)
It is propound a new method of assessment casual parameters of complex, unstable, moveable object for problems with structural identification of own object and synthesis of optimal, by structure, object stabilization system.